Development of an Educational Tourism-Based Practical Model on the Natural Phenomenon of Pink Beach to Improve High School Students' Chemical Process Skills and Literacy: Literature Review - Dini Sudianti; Muhammad Hendri Diarta; Gisna Haerani (Indonesian Journal of Teacher Education, 2026)
This study aims to examine the development of a beach edutourism-based practicum model to enhance senior high school students’ science process skills and chemical literacy. The method used in this study is a systematic literature review (SLR) by analyzing scientific articles published between 2016 and 2025. Data were collected from Google Scholar and ScienceDirect using relevant keywords and were selected according to predetermined inclusion and exclusion criteria. The results indicate that context-based and environmental learning approaches, such as outdoor learning, project-based learning, and problem-based learning, are effective in enhancing students’ chemical literacy, science process skills, and critical thinking abilities. Furthermore, the use of coastal natural phenomena as learning resources provides more authentic and meaningful learning experiences. In particular, the characteristics of Pink Beach, including its calcium carbonate-rich sand, offer relevant contextual examples for chemistry learning, especially in colloid systems. The beach edutourism-based practicum model enables the integration of chemical concepts with real-life contexts, making learning more relevant and engaging. Therefore, this model has strong potential as an innovative approach in chemistry education to meet the demands of 21st-century learning. Further research is needed to empirically test the effectiveness of this model in real classroom settings.